Techno-economic assessment of effervescent tablet-based nanofluids - Naser Ali; Husain Bahzad; Nawaf F. Aljuwayhel; Shikha A. Ebrahim (PLoS ONE, 2025)
The techno-economics of producing effervescent tablet-based nanofluids in start-up industries was investigated. The thermophysical properties, equipment costs, consumables, and operational expenditures for the production methods were determined. Electrical costs for running the devices were assessed based on the lowest, average, and highest prices worldwide. Key financial metrics, including accumulated project cost, interest, annual cost, operating expenses, production cost, payback and discounted payback periods, and internal rate of return (IRR) were calculated for different interest rates and amounts of sold products. The thermal performance under laminar and turbulent flow conditions and cost effectiveness were determined. The results showed that the effervescent tablet-based nanofluid was more favourable than its conventional counterpart. This is because of the lower equipment cost for the effervescent tablet process compared to its counterpart. The interest rate showed significant influence on the annual and product costs for both types of projects. Electrical cost had a minimal impact on the previous costs for both project cases. In addition, the effervescent tablet-based project outperformed its counterpart in terms of payback period, discounted payback period, IRR, and thermal performance, making it an optimal choice for investors and decision-makers.